Investigating Transport and Dissipation in the Subauroral E Region With Ionospheric Modification Experiments and Very High Frequency Radar Backscatter. Issue 3 (14th March 2019) - Hysell, D. L.; Munk, J.; McCarrick, M.
Abstract: Ionospheric modification experiments have been performed at the High‐Frequency Active Auroral Research Program (HAARP) facility in Gakona, Alaska, using a Very High Frequency (VHF) coherent scatter radar in Homer, Alaska, for experimental diagnostics. The experiments were intended to determine the threshold pump electric field required to initiate thermal parametric instability in the E region. The pump power level was ramped systematically to determine the threshold, and the experiment was repeated at four closely spaced pump frequencies. This provided threshold estimates at four E region altitudes. The theory for thermal parametric instability based on the work of Dysthe et al. (1983, https://doi.org/10.1063/1.863993 ) has been modified for application in the E region. The theory considers magneto‐ionic effects on the pump mode, linear mode conversion theory for upper hybrid wave generation, wave heating, and the effects of transport and dissipation based on fluid theory. The theory amounts to an eigenvalue problem where the eigenvalue is the threshold pump electric field for instability. The theory shows how the threshold depends on ionospheric transport coefficients and on the fractional cooling rate for inelastic electron‐neutral collisions. The theoretical predictions for threshold are roughly consistent with experimental values although the latter are probably affected by excess ionospheric absorption. Key Points: The threshold electric field for thermal parametric instability in the E region has been estimated experimentally A modified theory for thermal parametric instability in the E region has been formulated for comparison Comparisons between theory and measurements can be used to constrain transport, dissipation, and absorption in the ionosphere with remote sensing